Case Report: Wiskott-Aldrich Syndrome Caused by Extremely Skewed X-Chromosome Inactivation in a Chinese Girl - Hou, Xuening; Sun, Jie; Liu, Chen; Hao, Jihong (Frontiers in Pediatrics, 2021)
Wiskott-Aldrich syndrome (WAS) is a rare X-linked immunodeficiency disorder caused by abnormal expression of Wiskott-Aldrich syndrome protein due to WAS gene mutation, which is generally characterized by microthrombocytopenia, eczema, recurrent infections, and high risk of autoimmune complications and hematological malignancies. Although affected males with WAS usually manifest severe symptoms, female carriers have no significant clinical manifestations. Here, we describe a Chinese girl diagnosed with WAS carrying a heterozygous missense mutation in exon 2 of the WAS gene. The patient presented with persistent thrombocytopenia with small platelets and decreased WAS protein detected by flow cytometry and western blot analysis. The methylation analysis of the HUMARA gene displayed an extremely skewed X-chromosome inactivation (SXCI) pattern, where the X-chromosomes bearing normal WAS gene were predominantly inactivated, leaving the mutant gene active. Hence, our results suggest that completely inactivating the unaffected paternal X-chromosomes may be the reason for such phenotype in this female patient. SXCI has important implications for genetic counseling of female carriers with a family history of WAS.